Leadership development through talent development and succession planning strategies in national secondary schools - Armugam, Banu (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
Succession planning is a strategic planning for identifying and developing future leaders at all levels in organizations. It is used to address the uncertain changes in organizations due to employees resign, retire, sick or die. Any organization without a formal succession planning system in place will find problem in many areas such as: key positions are not filled on time, key positions are filled by external candidates, prospective candidates not prepared, high turnover rates and no required talent, skills, competencies and qualified talent is not retained. These are some of the problem areas which educational organizations face and never realize. This is due to lack of formal planning. Therefore, the study seeks to reveal the relationship of leadership development through talent development and succession planning strategies in national schools. Previous qualitative and survey data supported leadership development for effective succession planning. The findings indicated individual potential leadership elements need to be enhanced and developed further. Therefore, this study will use quantitative method to determine leadership development contributing to succession planning. Succession planning is just not one exclusive process but it needs to be linked with other components such as talent development and leadership development to be successful. Talent development as the need to identify and develop talent pools that meet the current and future leadership requirement in the school. In addition, leadership development contributing to organizational succession planning. Therefore, such linking makes succession planning wholesome and more efficient but most of the education system do not link it completely.